A Case Series Study of Weekly or Fortnightly Transcranial Magnetic Stimulation (TMS) in Major Depressive Disorder - Yvonne Turnier-Shea; Gregory M. Peterson; Marzena Rybak; Saxby Pridmore (Brain Sciences, 2024)
Background: Major depressive disorder (MDD) is frequently chronic and relapsing. The use of maintenance or continuation transcranial magnetic stimulation (TMS) has received clinical and some research support. Objective: To conduct a case series study to report the outcomes of once-weekly (OW) or once-fortnightly (OF) continuation TMS in a real-life setting. Methods: We offered OW or OF TMS sessions to patients with MDD in remission or partial remission/relapse. Results: Ten patients received OW TMS and four received OF TMS, for 8 to 46 weeks. No patients in either group who were in remission or partial remission at baseline experienced a relapse. Improvements in HAMD6 and CGI-S scores were statistically significant or of borderline significance for the total sample and the OW group. Conclusions: This naturalistic, open-label observational study indicates that OW TMS is effective as maintenance therapy in MDD, while also offering some support for OF TMS maintenance in preventing relapse.